An Analysis of Students’ Narrative Text Translation from English to Indonesian at the Tenth Grade Students of SMA Pangeran Antasari - Indra Sihombing Nababan; Ernita Indah Sari Nainggolan ; Fachri Yunanda (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to explore the diverse translation method strategies utilized by students in the tenth grade at SMA Pangeran Antasari. The study was conducted using a qualitative descriptive methodology. Participants included tenth-grade students from SMA Pangeran Antasari. The research employed two tools: the initial test involved the translation of English texts into Bahasa, while the subsequent questionnaire comprised ten questions. During the examination of translation techniques, the study applied the translation method framework as proposed by Newmark. The outcomes indicated that students employed merely four distinct methods to translate the texts. The approaches to translation adopted in this study encompass Literal Translation, Faithful Translation, Word-for-Word Translation, and Free Translation. Data examination demonstrates that among the 10 participants, Literal Translation and Faithful Translation were the primary translation methods used. Conversely, Word-for-Word Translation and Free Translation served as the secondary techniques. These findings suggest a diverse application of translation methods by the students on the narrative text